Quantifying effects of compositional variations on microstructural properties of polypropylene-wood fiber composites by melt rheology and tensile test data. (February 2019) - Durmus, Ali; Ozcan, Mehmet; Aydin, Ismail
In this study, melt-state rheological behavior and solid-state mechanical properties of polypropylene-wood fiber composites were investigated in detail depending on compositional variations such as (i) alkaline treatment on wood fibers, (ii) fiber size, (iii) wood fiber content, and (iv) compatibilizer/wood fiber ratio. Composite samples were prepared in a lab-scale co-rotating twin screw extruder by using a maleic anhydride grafted polypropylene as compatibilizer. Morphological features of composites were examined in a scanning electron microscopy. Viscoelastic behavior and mechanical properties of samples were analyzed by performing oscillatory tests in a rotational rheometer and a universal tensile test machine. It was found that the increasing amounts of wood fiber and compatibilizer/wood fiber ratio led to improve melt elasticity and tensile strength. It was concluded that the amount of compatibilizer into composite formulation was the most important compositional parameter compared to size and chemical treatment of wood fibers for improving the physical properties of composites. The Nicolais-Nicodemo micromechanical model showed that the increasing amount of compatibilizer yielded lower parameters which implied better interfacial adhesion between polypropylene and wood fibers.